Analysis and interpretation of the 2022 Global Cancer Statistics Report： cancer burden and epidemiological trends in China and the world - WU Qi, FAN Bonan, LI Yan (Zhenduanxue lilun yu shijian, 2025)
In February 2024, the International Agency for Research on Cancer (IARC) released the 2022 Global Cancer Statistics Report. In 2022, there were nearly 20 million new cancer cases and 9.7 million deaths. The report provides statistics on the incidence and mortality of 36 different types of cancer in 185 countries around the world, analyzing geographic, gender-based, and Human Development Index (HDI)-related differences. It also predicts the global burden of cancer disease by 2050. Demographic forecasts suggest that by 2050, the number of new cancer cases worldwide is expected to reach 35 million annually-an increase of 77% compared to 2022. Geographically, cancer incidence and mortality rates show significant regional disparities. In 2022, nearly half (49.2%) of the world's new cases and the majority (56.1%) of cancer deaths occurred in Asia. In terms of gender distribution, the overall cancer incidence and mortality rate among females were lower than those among males in 2022. With respect to HDI, the risk of developing cancer increases with higher HDI levels. In 2022, the top 5 newly diagnosed cancer cases worldwide are lung cancer, female breast cancer cancer, colorectal cancer, prostate cancer, gastric cancer in turn. There were nearly 2.5 million new lung cancer cases and over 1.8 million related deaths. Breast cancer in women accounted for 2.3 million new cases and nearly 670 000 deaths. Colorectal cancer, including anal cancer, had more than 1.9 million new cases and over 900 000 deaths. Prostate cancer recorded 1.5 million new cases and nearly 400 000 deaths. There were nearly 970 000 newly-diagnosed cases of gastric cancer and 660 000 related deaths. In China in 2022, lung cancer still ranks first in the cancer incidence spectrum in China, accounting for 22.0% of the total new cases of cancer in China. This proportion has further increased compared to 2018 data (17.9%), followed by colorectal cancer (10.7%), thyroid cancer (9.7%), liver cancer (7.6%), and gastric cancer (7.4%), which account for more than half of the total new cases in China (57.4%). This paper reviews the data sources and statistical methods used in the report, interprets the epidemiological trends of major cancer types, and analyzes the incidence and burden of major cancers prevalent in China, provi-ding an overview of their disease burden and epidemiological trends.